Towards Identifying Quality Assurance Standards in Virtual Learning Environments for Science Education. - Al-Hosan, Amani; Oyaid, Afnan (Pertanika Journal of Social Sciences & Humanities, 2012)
Many studies indicated the beneficial impacts of Virtual Learning Environments (VLE) on teaching and learning experience (Barbour & Reeves, 2009). Therefore, quality and standardisation of e-learning have become a crucial success factor to ensure the quality of learning and to maximize benefits gained from such learning experience. This research sought to identify and propose a set of standards for VLEs in science education so as to ensure the quality of these environments and maximize the learning benefits for students. A wide range of studies have been analyzed in order to identify the main dimensions of VLE from which quality standards should be derived. Hence, an evaluation form with six main standards was developed based on previous studies. It was then distributed to purposively selected panel of experts who ranked on a 3-point scale and determined the importance of each standard. The ranking of these standards was done by the panel of experts from Saudi, European, and Malaysian universities with different backgrounds. These standards, arranged in their order of importance, are: design, support, authority and safety, improvement and review, VLE cost effectiveness, and quality VLE software. Moreover, the findings indicated that the devised form is suitable to be used as an evaluation tool to assess the quality of VLE for science education.